If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 10 + 1 = 7 Reorder the terms: 10 + 1 + y = 7 Combine like terms: 10 + 1 = 11 11 + y = 7 Solving 11 + y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + y = 7 + -11 Combine like terms: 11 + -11 = 0 0 + y = 7 + -11 y = 7 + -11 Combine like terms: 7 + -11 = -4 y = -4 Simplifying y = -4
| 5-2b=b+1 | | 2(3n-2)=24 | | 3(5y+2)=60 | | 10x^2-21x-10= | | 15x^2-6x-9= | | 7x+10-2x=5 | | -x+6=2x-4*(-3) | | (x-3)(x-6)= | | 4.3x+0.8y+5.3=0 | | 2x^2-8x-72=0 | | 128x^3-2y^3= | | q^3r^3-125= | | 4x-50+2z=180 | | y=7-10 | | 33.7-(1.5s+2.3)=3.4a-(0.4-5.7) | | 12(x)=1.67 | | 77x^2-60x-32= | | 4=m-14 | | 6x^3+36x^2+30x= | | 3/5x^2-1/10x=1/2 | | 2x^2+5x-6=-x^2+13x-7 | | x^4-2x^3+x^2=2 | | -12v^2+2=5v | | y=2x^2+5x-6 | | 4y-8+xy-2x= | | 12y^3-y^2-6y=0 | | 4x^2+88x+420=1380 | | 2x-17=4x | | -9a+b=35 | | 9a+5b=13 | | (8i-14)+(2i-6)= | | 4cos(t)= |